A SYSTEMATIC REVIEW OF REFUGEE EDUCATION IN MALAYSIA - Thavamalar Thuraisingam (Jurnal EL-RIYASAH, 2022)
The present study is focused on the issue of refugee education in Malaysia and the premise for this study is rooted in SDG 4. As Malaysia has not ratified the 1951 United Nations convention and is not a signatory of its 1967 Protocol, refugee children in the country are unable to access public school systems. Their only means to obtain an education is via an informal parallel system of refugee community learning centres that are run across the country. It is therefore pertinent for policymakers, NGOs, UNHCR Malaysia and local communities to have a clear understanding of the issues concerning refugee education to propose sustainable solutions to ensure that no refugee child in Malaysia is left behind. A systematic literature review approach, guided by the PRISMA statement 2020 was adopted in this study to better understand the phenomenon of concern and outline the key barriers and facilitators in the context of refugee education in Malaysia. A total of 14 articles met the selection criteria and were within the scope of the research question. A thematic analysis was conducted and several themes emerged. The review acknowledges that the educational needs of refugee children in Malaysia warrant attention.